China’s Understanding of International Humanitarian Intervention: A Case Study of Darfur - Alparslan, Neslihan Topcu (Fırat Üniversitesi, 2025)
After the Second World War, many countries attained statehood through the declaration of independence, increased economic difficulties, famine, authoritarian governments, etc. and due to these issues, human rights violations have increased. States in various parts of the world not to protect their citizens or to attack their citizens’ rights has required the international community to get involved in this issue. In this context, the United Nations carries out a work on humanitarian intervention, and the members of the United Nations Security Council play an important role in the presence or absence of humanitarian intervention. This paper examines the attitude of China towards humanitarian intervention as a member of the United Nations Security Council. This study seeks to address the question of what the Darfur issue changed in China’s understanding of humanitarian intervention, by examining the period before and after the crisis.

İkinci Dünya Savaşı sonrasında birçok ülkenin bağımsızlıklarını ilan ederek devlet vasfı kazanması, ekonomik zorlukların artması, kıtlık, baskıcı hükümetler ve benzeri sorunlarla beraber insan hakları ihlâlleri çoğalmıştır. Dünyanın çeşitli bölgelerinde devletlerin halkını koruyamaması veya bizzat halkının haklarına saldırması, uluslararası toplumun bu konuya müdahil olmasını gerektirmiştir. Bu kapsamda özellikle Birleşmiş Milletler, insani müdahaleye yönelik çalışmalar yürütmekte ve Birleşmiş Milletler Güvenlik Konseyi üyeleri, insani müdahalenin olması veya olmaması noktasında önemli bir rol oynamaktadır. Bu çalışma ise Birleşmiş Milletler Güvenlik Konseyi üyelerinden biri olan Çin’in insani müdahaleye yönelik tutumunu incelemektedir. Bu bağlamda, çalışmanın temel sorusu, örnek olay olarak seçilen Darfur sorunu öncesinde ve sonrasında Çin’in insani müdahaleye ilişkin yaklaşımının nasıl bir değişim gösterdiğidir.
ÇİN’İN ULUSLARARASI İNSANİ MÜDAHALE ANLAYIŞI: DARFUR ÖRNEĞİ
Keywords: International Law; Uluslararası Hukuk